2003
DOI: 10.1097/01.sap.0000058501.64655.31
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Scrotal Remnant as a Tissue-Expanding Musculocutaneous Flap for Scrotal Reconstruction in Pagetʼs Disease

Abstract: Wide excision of extramammary Paget's disease of the penoscrotal region may leave large defects that cannot be closed easily. The authors describe their experience with a series of 6 patients in whom reconstruction of the scrotal defect was undertaken using the scrotal remnant raised as a stretchable musculocutaneous flap. It was observed that as little as a third of the residual scrotum could be expanded to resurface the entire scrotum. All flaps survived completely. Severe scrotal edema and ecchymosis were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 11 publications
0
16
0
7
Order By: Relevance
“…As little as one-third of residual scrotum can be stretched to resurface the entire scrotum. 13 Excessive undermining and suturing under tension, however, may lead to flap loss or wound edge necrosis. 3 This flap is technically easy with less donor site morbidity and other complications.…”
Section: Discussionmentioning
confidence: 99%
“…As little as one-third of residual scrotum can be stretched to resurface the entire scrotum. 13 Excessive undermining and suturing under tension, however, may lead to flap loss or wound edge necrosis. 3 This flap is technically easy with less donor site morbidity and other complications.…”
Section: Discussionmentioning
confidence: 99%
“…The primary treatment is surgical excision. 7,9,11,[14][15][16][17] Non-surgical methods are also used but only in a few cases. Hata reported that radiotherapy was a curative therapy in 22 patients with EMPD.…”
Section: Complicationsmentioning
confidence: 99%
“…The common methods are skin grafting, burying them underneath the medial thigh skin, tissue expansion of adjacent tissues and use of local fasio-cutaneous or musculo-cutaneous flaps. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] Local pedicled fascio-cutaneous flaps from the thigh and the groin area offer the advantages of avoiding skin graft problems, preserving adequate sensation, and covering a large defect.…”
Section: Introductionmentioning
confidence: 99%